Konsentrasi Perekat Tapioka Terhadap Kualitas Briket Arang Tunggul Batang Kelapa - Difa Febrian Febrian; Faizah Hamzah Hamzah; Farida Hanum Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
This study aims to obtain the best tapioca adhesive concentration in making charcoalbriquettes. This research was conducted experimentally using a completely randomized design method consisting of 5 treatments and 3 replications in order to obtain 15 experimental units. The treatment in this study was the ratio of coconut stem charcoal and tapioca adhesive as follows: P1 (97:3), P2 (95:5), P3 (93:7), P4 (91:9), and P5 (89:11). The parameters observed in this study were moisture content, ash content, volatile matter content, bound carbon content, density, and heating value. The results showed that the addition of tapioca adhesive concentration gave significantly different results for all parameters. The best quality is the composition of P1 with composition rate of 97:3 having water content of 4,17%, ash content of 5,21%, vaporizing substance 9,11%, carbon content of 80,49%, density of 0,593 g/cm3and the heating value is 6.350 cal/g. Key words: Coconut stem charcoal, tapioca, briquettes